Condición jurídica de las afectaciones viales: Análisis de una potencial expropiación anticipada - Reátegui Pilco, Jorge (2024)
In this article, the author analyzes the roadway affectations, establishing the main differences with the cession for roads and with the expropriation procedures promoted by the State. In this sense, urban development procedures do not represent an obstacle for the subsequent initiation of an expropriation procedure, even though they may be executed in the medium or long term. In addition, the importance of taking into account such road affectations with a view to the exercise of the right of ownership by the owners or possessors of the real estate included in such affectation is also considered.